IMPLEMENTASI TELEGRAM NOTIFICATION ALERT PADA NETWORK MONITORING SYSTEM DENGAN NAGIOS - Bakhtiar Rifai; Nanang Nuryadi; Amarulloh Ripai (Jurnal Mantik Penusa)
A healthy data center will greatly help the performance of employees and network administrators. The Inspectorate General of the Ministry of Education and Culture does not have a network monitoring system in the data center. The absence of a system for monitoring each device in the data center, the data center condition will become unhealthy. If the condition of the server, router, and switch devices are not functioning properly the network administrator cannot know in real-time. It requires network monitoring system with plugin support that can help network administrators do their work. Nagios is a network monitoring system that has a variety of features and can be configured with social media such as telegram because it supports API bots from python, namely twx. When the hardware or software is experiencing problems or down, eating Nagios will send notifications via the bot account that has been created and synchronized with Bash Nagios.